Childhood obesity: a health care centre reality. - Branco, Susana; Jorge, Maria do Sameiro; Chaves, Helena (Acta Médica Portuguesa, 2011)
Childhood obesity is an important public health issue, especially in developed countries, with a multifactorial nature. We purpose to evaluate the prevalence of overweight and obesity in a group of children and analyze related risk factors.Study including 207 children aged 5-6 years old enrolled in Urban Extension of ACES Ave III - Famalicão. Data were collected from connector plugs school health and phone interview of parents.Cross sectional observational study. Statistical analysis was performed using SPSS software and parametric tests were used to verify the statistical significance of data, considering statistical significance for p values <0.05.The overall prevalence of overweight was 46.9% and obesity 28.5%, and the majority were girls. Odds ratio revealed that obesity risk increased with birthweight (<2500 g: 1.28; 2500-3000 g: 1.84; 3000 g-3500 g: 1.83; 3500 g-4000 g: 2.00 ), the number of hours of sleep (<9 hours: 1.5, 9-10 hours: 1.75;> 10 hours: 1.89), the number of hours of television (<2 hours: 1.71; 2-4 hours: 1.81;> 4 hours: 1.89) and intake of fruit juice as the main drink (not: 1.70; yes: 1.80). The obesity risk was higher when parents were overweight and obese (father/mother: normal-weight: 1.58 / 1.62; pre-obese: 1.93 / 2.10, obese: 1.86 / 1 79), lived in rural areas (urban: 1.67, rural: 1.75) and have basic education (father/mother: 1st-4th class: 2.20 / 2.58, 5th 9th class: 1.80/ 1.69; 10th-12th class: 1.38 / 1.65; university: 1.78 / 1.76). There was a association between the number of siblings and obesity (zero: 1.84; a: 1.68; two: 1.87; three: 1.75). The physical activity acted as a protective factor for obesity (practice: 1.74; not practice: 1.78).The results of this study revealed the need for immediate implementation of measures involving health professionals, parents and educators. Knowledge of various risk factors allows for the adoption of preventive strategies to mitigate the impact of childhood obesity.